Primer-topcoat solvent-free oil-resistant static-conductive phenolic epoxy coating
By using bottom-to-one solvent-free oil-resistant electrostatic conduction phenolic epoxy coating, the electrostatic problems in the petroleum and petrochemical industry are solved, and the corrosion resistance of the coating film is achieved, with excellent electrostatic conduction and corrosion resistance and excellent electrostatic conduction capabilities and Environmentally friendly performance.
Patent Information
- Application Number
- CN202411748201.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
AI Technical Summary
The existing technology is difficult to effectively solve the static problem in the petroleum and petrochemical industry, and it also has anti-corrosion properties that are resistant to oil, acid and alkali and temperature differences.
A bottom-side-in-one solvent-free oil-resistant electrostatic phenolic epoxy coating consists of component A and component B. Component A includes solvent-free liquid phenolic epoxy resin, low viscosity solvent-free flexible epoxy resin, needle Component B includes modified alicyclic amine and 2,4,6-tris(dimethylaminomethyl)phenol.
The coating maintains corrosion resistance in an environment with large temperature difference, has excellent electrostatic conduction ability, salt spray resistance, environmentally friendly and high corrosion resistance, and can effectively reduce the harm of solvents to the human body.
Smart Images

Figure CN119463645A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin coatings, and more specifically to a bottom-to-top integrated solvent-free, oil-resistant, and static-conductive phenolic epoxy coating. Background Art
[0002] Epoxy resin coatings are widely used in the fields of petroleum and petrochemicals, automobile industry, shipbuilding industry and steel structure anti-corrosion due to their excellent chemical resistance, good thermal stability and electrical insulation, and strong adhesion to metal substrates. Compared with ordinary bisphenol A epoxy coatings, phenolic epoxy coatings have a large cross-linking density after cross-linking and curing with amine curing agents, high film density, and higher heat resistance and chemical resistance than ordinary bisphenol A epoxy resins. Phenolic epoxy resin coatings not only inherit the advantages of good adhesion of ordinary bisphenol A epoxy coatings, but also have better acid resistance, alkali resistance, gasoline resistance, and corrosion resistance. Therefore, they are widely used in industries such as the petroleum and petrochemical industry that have strict requirements on product performance. Due to the special nature of products in the petroleum and petrochemical industry, it is required that the static electricity generated in oil storage tanks and oil pipelines can be dissipated in time, and there are high requirements for electrochemical corrosion resistance, acid and alkali resistance, temperature difference resistance, etc. A bottom-to-top integrated solvent-free oil-resistant static conductive phenolic epoxy coating that meets environmental protection and use requirements came into being. Summary of the invention
[0003] In order to overcome the deficiencies of the prior art, the present invention provides a bottom-and-top integrated solvent-free, oil-resistant, static-conductive phenolic epoxy coating.
[0004] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating, a bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating, composed of component A and component B;
[0005] The weight proportions of the raw materials in component A are as follows: solvent-free liquid phenolic epoxy resin: 25-35 parts, low-viscosity solvent-free flexible epoxy resin: 5-10 parts, epoxy reactive diluent: 3-8 parts, needle-shaped nano titanium dioxide: 5-10 parts, precipitated barium sulfate: 5-10 parts, mica powder: 30-40 parts, structured acrylic copolymer dispersant: 0.1-1 parts, silicone defoamer: 1-1.5 parts, polyamide wax powder: 0.1-1 parts, modified silicone leveling agent: 0.1-1 parts, siloxane coupling agent: 0.1-1 parts;
[0006] The weight proportions of the raw materials in component B are as follows: modified alicyclic amine: 95 to 100 parts, 2,4,6-tris(dimethylaminomethyl)phenol: 1 to 5 parts.
[0007] As a preferred technical solution of the present invention, the particle size of the precipitated barium sulfate is 1100 mesh to 1300 mesh, and the particle size of the mica powder is 350 mesh to 450 mesh.
[0008] As a preferred technical solution of the present invention, the present invention also proposes a processing technology for a bottom-to-top integrated solvent-free oil-resistant electrostatic conductive phenolic epoxy coating, comprising the following steps:
[0009] Step 1, weigh each raw material according to the proportion;
[0010] Step 2: adding solvent-free liquid phenolic epoxy resin, low-viscosity solvent-free flexible epoxy resin, epoxy reactive diluent, structured acrylic copolymer dispersant, precipitated barium sulfate, and organosilicon defoamer into a batching kettle in sequence under stirring conditions, and stirring sufficiently;
[0011] Step 3: further blending and grinding the mixed slurry obtained in step 2 on a sand mill, and finally filtering to obtain a premixed slurry;
[0012] Step 4: Add needle-shaped nano titanium dioxide, mica powder, modified silicone leveling agent, polyamide wax powder, and siloxane coupling agent to the premixed color slurry prepared in step 3 in sequence under stirring, stir thoroughly, filter, and package to obtain component A;
[0013] Step 5, adding modified alicyclic amine and 2,4,6-tris(dimethylaminomethyl)phenol to a batching kettle in sequence, stirring thoroughly, filtering and packaging to obtain component B;
[0014] Step 6: Mix component A and component B in a ratio of 1:0.2-0.3, and mechanically stir and mix them evenly to obtain the prepared epoxy coating.
[0015] As a preferred technical solution of the present invention, in the step 2, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 15 min to 25 min.
[0016] As a preferred technical solution of the present invention, in the step three, filtering and screening is performed after the fineness does not exceed 60 μm.
[0017] As a preferred technical solution of the present invention, in the step 4, the stirring speed is 1800 rpm to 2200 rpm, and the stirring time is 25 min to 35 min.
[0018] As a preferred technical solution of the present invention, in the step five, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 5 min to 15 min.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention is a solvent-free coating, which reduces the harm of solvents to the human body and has a certain environmental protection effect; the introduction of low-viscosity solvent-free flexible epoxy resin can reduce the viscosity of the coating on the one hand, and reduce the rigidity of the coating on the other hand, and can effectively maintain the anti-corrosion performance in an environment with a large temperature difference; the introduction of active diluent can avoid migration and precipitation into the medium, and does not pollute the medium; the addition of needle-shaped nano titanium dioxide, on the one hand, plays a covering role similar to titanium dioxide, and on the other hand, the needle-shaped results can be effectively overlapped to increase the electrostatic conductivity of the coating after drying, and at the same time, the photocatalytic property and super hydrophilicity of the nano titanium dioxide can enhance the self-cleaning effect of the coating, greatly saving cleaning costs; the addition of high-content mica powder can effectively improve the shielding effect of the coating, and can make the salt spray resistance of the system reach 3000h, and can make the prepared coating have excellent protective performance, and has environmental protection, high corrosion resistance, excellent resistance to heat acid, hot alkali, and gasoline, strong electrostatic conductivity, and does not pollute the medium compared with traditional graphite-based electrostatic conductive materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the molecular structure of the solvent-free liquid phenolic epoxy resin of the present invention;
[0021] Figure 2 Schematic diagram of the molecular structure of the low-viscosity solvent-free flexible epoxy resin of the present invention;
[0022] Figure 3 This is the infrared spectrum of the modified alicyclic amine of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] like Figures 1 to 3 As shown, the present invention provides a bottom-to-top integrated solvent-free oil-resistant electrostatic conductive phenolic epoxy coating, which is composed of component A and component B;
[0025] The weight proportions of the raw materials in component A are as follows: solvent-free liquid phenolic epoxy resin: 25-35 parts, low-viscosity solvent-free flexible epoxy resin: 5-10 parts, epoxy reactive diluent: 3-8 parts, needle-shaped nano titanium dioxide: 5-10 parts, precipitated barium sulfate: 5-10 parts, mica powder: 30-40 parts, structured acrylic copolymer dispersant: 0.1-1 parts, silicone defoamer: 1-1.5 parts, polyamide wax powder: 0.1-1 parts, modified silicone leveling agent: 0.1-1 parts, siloxane coupling agent: 0.1-1 parts;
[0026] The weight proportions of the raw materials in component B are as follows: modified alicyclic amine: 95 to 100 parts, 2,4,6-tris(dimethylaminomethyl)phenol: 1 to 5 parts.
[0027] Wherein, the particle size of the precipitated barium sulfate is 1100-1300 mesh, and the particle size of the mica powder is 350-450 mesh.
[0028] The present invention also discloses a processing technology for a bottom-to-top integrated solvent-free, oil-resistant, and static-conductive phenolic epoxy coating, comprising the following steps:
[0029] Step 1, weigh each raw material according to the proportion;
[0030] Step 2: adding solvent-free liquid phenolic epoxy resin, low-viscosity solvent-free flexible epoxy resin, epoxy reactive diluent, structured acrylic copolymer dispersant, precipitated barium sulfate, and organosilicon defoamer into a batching kettle in sequence under stirring conditions, and stirring sufficiently;
[0031] Step 3: further blending and grinding the mixed slurry obtained in step 2 on a sand mill, and finally filtering to obtain a premixed slurry;
[0032] Step 4: Add needle-shaped nano titanium dioxide, mica powder, modified silicone leveling agent, polyamide wax powder, and siloxane coupling agent to the premixed color slurry prepared in step 3 in sequence under stirring, stir thoroughly, filter, and package to obtain component A;
[0033] Step 5, adding modified alicyclic amine and 2,4,6-tris(dimethylaminomethyl)phenol to a batching kettle in sequence, stirring thoroughly, filtering and packaging to obtain component B;
[0034] Step 6: Mix component A and component B in a ratio of 1:0.2-0.3, and mechanically stir and mix them evenly to obtain the prepared epoxy coating.
[0035] Wherein, in step 2, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 15 min to 25 min.
[0036] Among them, in step three, filtering and screening are carried out after the fineness does not exceed 60μm.
[0037] Wherein, in step 4, the stirring speed is 1800rpm~2200rpm, and the stirring time is 25min~35min.
[0038] Wherein, in step five, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 5 min to 15 min.
[0039] Solvent-free liquid novolac epoxy resin is a low molecular weight phenol-type novolac epoxy resin with an epoxy equivalent of 168-178. The molecular structure of solvent-free liquid novolac epoxy resin is as follows: Figure 1 As shown; compared with ordinary bisphenol A epoxy resin, the solvent-free liquid phenolic epoxy resin has a more regular molecular structure and a high cross-linking density after curing, and the formed coating has excellent heat resistance, solvent resistance, and chemical resistance.
[0040] Low viscosity solvent-free flexible epoxy resin is a low viscosity small molecule epoxy resin with an epoxy equivalent of 350-500. The structural formula is as follows Figure 2 As shown, the chain 8 carbons in the structure separate the rigid aromatic groups, thereby obtaining chain toughness. After being mixed with solvent-free liquid phenolic epoxy resin, it reacts with modified alicyclic amine during film curing, which will not damage the performance of the product and can increase the toughness of the system. The introduction of low-viscosity solvent-free flexible epoxy resin can reduce the viscosity of the coating on the one hand, and reduce the rigidity of the coating on the other hand, which can effectively maintain the anti-corrosion performance in an environment with a large temperature difference.
[0041] The modified alicyclic amine is 2634. Compared with its polyamide counterparts, alicyclic polyamines have the characteristics of better chemical resistance, faster curing speed, higher hardness and better adhesion. Although phenolic amine curing agents can be cured in low temperature and humid environments and have a fast drying speed, they have greater cohesive strength when used with phenolic epoxy and poor paint film adhesion. The present invention selects modified alicyclic amine 2634 that can be fully cured at room temperature and has excellent chemical resistance after drying, and adds 2,4,6-tris(dimethylaminomethyl)phenol as a curing accelerator as component B in the curing agent system. The infrared spectrum of the modified alicyclic amine is as follows: Figure 3 shown.
[0042] Needle-shaped nano titanium dioxide is a conductive material coated with SnO2 / Sb conductive layer on the surface of rutile titanium dioxide. Its nano-scale particle size distribution makes it have better dispersibility, and its needle-shaped structure has better conductivity than other shape structure products. The addition of needle-shaped nano titanium dioxide, on the one hand, plays a covering role similar to titanium dioxide, and on the other hand, the needle-shaped structure can effectively overlap, increase the static conductivity of the coating after drying, and does not pollute the medium compared with traditional graphite static conductive materials. At the same time, the photocatalytic and super hydrophilic properties of nano titanium dioxide can enhance the self-cleaning effect of the coating, greatly saving cleaning costs. The introduction of epoxy active diluent can reduce the viscosity of the system and participate in the curing film, avoiding migration and precipitation into the storage medium, and does not pollute the medium. The addition of high-content mica powder can effectively improve the shielding effect of the coating, and can make the salt spray resistance of the system reach 3000h, and can make the prepared coating have excellent protective properties. The preparation method is simple and feasible, and it is a primer-top integrated coating, which does not need to be coated with a topcoat. A single-layer film can meet the coating requirements, greatly saving labor costs.
[0043] The bottom-to-top integrated solvent-free oil-resistant and static-conducting phenolic epoxy coating prepared by the present invention has excellent protective performance and is suitable for the inner wall of oil storage tanks and the inner wall of oil pipelines, etc., which have high requirements for corrosion resistance, oil resistance, acid and alkali resistance and static-conducting performance. The performance is shown in the following table after testing:
[0044] project This example Film thickness(um) 250um Surface dry(h) 2.5h Work hard (h) 13h Pencil hardness 3H Abrasion resistance (1000g / 1000r, g) 23mg Adhesion (Pull-off method) 13MPa Gasoline resistance (60±2℃, 30d) 30d paint film has no abnormality Resistant to 10% sulfuric acid (60±2℃, 30d) 30d paint film has no abnormality 10% sodium chloride (95±2℃, 30d) 30d paint film has no abnormality Resistant to 10% sodium hydroxide solution (60±2℃, 30d) 30d paint film has no abnormality High temperature and high pressure resistance (120℃ tap water, 0.25MPa, 30d) 30d paint film has no abnormality Heat resistance (230℃, 168h) 168h paint film has no abnormality Salt spray resistance (3000h) 3000h paint film without blistering, rust or shedding Surface resistivity(Ω) 108
[0045] The invention is a solvent-free coating, which reduces the harm of solvents to human body and has a certain environmental protection effect.
[0046] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating, characterized in that: It is composed of component A and component B; The weight proportions of the raw materials in component A are as follows: solvent-free liquid phenolic epoxy resin: 25-35 parts, low-viscosity solvent-free flexible epoxy resin: 5-10 parts, epoxy reactive diluent: 3-8 parts, needle-shaped nano titanium dioxide: 5-10 parts, precipitated barium sulfate: 5-10 parts, mica powder: 30-40 parts, structured acrylic copolymer dispersant: 0.1-1 parts, silicone defoamer: 1-1.5 parts, polyamide wax powder: 0.1-1 parts, modified silicone leveling agent: 0.1~1 part, siloxane coupling agent: 0.1~1 part; The weight proportions of the raw materials in component B are as follows: modified alicyclic amine: 95 to 100 parts, 2,4,6-tris(dimethylaminomethyl)phenol: 1 to 5 parts.
2. The bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy paint according to claim 1, characterized in that: The particle size of the precipitated barium sulfate is 1100-1300 meshes, and the particle size of the mica powder is 350-450 meshes.
3. The processing technology of the bottom-to-top integrated solvent-free oil-resistant electrostatic conductive phenolic epoxy coating according to any one of claims 1 to 2, characterized in that: The steps include: Step 1, weigh each raw material according to the proportion; Step 2: adding solvent-free liquid phenolic epoxy resin, low-viscosity solvent-free flexible epoxy resin, epoxy reactive diluent, structured acrylic copolymer dispersant, precipitated barium sulfate, and organosilicon defoamer into a batching kettle in sequence under stirring conditions, and stirring sufficiently; Step 3: further blending and grinding the mixed slurry obtained in step 2 on a sand mill, and finally filtering to obtain a premixed slurry; Step 4: Add needle-shaped nano titanium dioxide, mica powder, modified silicone leveling agent, polyamide wax powder, and siloxane coupling agent to the premixed color slurry prepared in step 3 in sequence under stirring, stir thoroughly, filter, and package to obtain component A; Step 5, adding modified alicyclic amine and 2,4,6-tris(dimethylaminomethyl)phenol to a batching kettle in sequence, stirring thoroughly, filtering and packaging to obtain component B; Step 6: Mix component A and component B in a ratio of 1:0.2-0.3, and mechanically stir and mix them evenly to obtain the prepared epoxy coating.
4. The processing technology of the bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating according to claim 3 is characterized in that: In the step 2, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 15 min to 25 min.
5. The processing technology of the bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating according to claim 3 is characterized by: In the step 3, filtering and screening is performed after the fineness does not exceed 60 μm.
6. The processing technology of the bottom-to-top integrated solvent-free oil-resistant static-conducting phenolic epoxy coating according to claim 3 is characterized by: In the step 4, the stirring speed is 1800 rpm to 2200 rpm, and the stirring time is 25 min to 35 min.
7. The processing technology of the bottom-to-top integrated solvent-free oil-resistant static-conductive phenolic epoxy coating according to claim 3 is characterized by: In the step 5, the stirring speed is 800 rpm to 1200 rpm, and the stirring time is 5 min to 15 min.
Citation Information
Patent Citations
Solvent-free phenolic epoxy electrostatic conductive coating formula and preparation method thereof
CN107043586A
Anti-static coating
CN107057502A
Cited By
Low viscosity high performance solventless epoxy coating and method of making same
CN122726777A